Pengembangan Access Open Journal System (AOJS) sebagai Sistem Indeksasi dan Manajemen Pengelolaan Publikasi Jurnal (Yayasan Kawanad, 2022)
Open Journal Systems (OJS) is a web-based content management system specifically designed to handle the entire scientific publication management process. The Ministry of Research, Technology and Higher Education has also developed its own index, namely the SINTA (Science and Technology Index) which is expected to not only refer to the Scopus journal index. The relationship between Access Indexing and OJS is inseparable where OJS is a facility in managing journal publications and Access Indexing is a feature for disseminating journal articles in journal searches. This study tries to build an Access Open Journal Systems (AOJS) model that can be used as a form of publication and publishing management in international indexing. The application allows updating of data/content and sharing from various online journal sources. Access Open journal systems (AOJS) can allow end users, and still refer to international publishing management standards. Broadly speaking, this research is divided into three stages, namely pre-development data collection, development and implementation, and post-development data collection. From the results of the study, it has succeeded in developing an Access Open Journal System (AOJS) application by promoting simple features so that journal managers can manage journals well. We also removed the quick publish/submit module which we felt could worsen journal management properly. The OAI feature is also used for indexing so that metadata can be retrieved by multiple indexers. The Access Open Journal System (AOJS) that was built has a fairly easy configuration for its application and service modules, this configuration can make it easier for journal managers to create dynamic content and can be tailored to the needs of each manager.